THE CHANGE IN THE CONCENTRATION OF PHOSPHOLIPIDS IN EXPERIMENTAL INFECTION OF LAMBS WITH ECHINOCOCCOSIS AND PAECILOMYCES - Vakhidova Adolat Mamatkulovna; Khudoyarova Gavhar Nurmamatovna; Mamedov Arzu Nazirovich (Scholar Express Journals, 2022)
Mechanisms of action on tissues caused by helminths are known to lead to atrophic changes. Especially sharp atrophy is observed in echinococcosis. At the same time, along with mechanical destruction and compression ischemia of tissues adjacent to the bodies of helminths, irreversible necrobiotic or necrotic changes occur due to toxic effects on the host body. At the same time with mechanical damage to tissues disturbed by helminthiasis, productive and inflammatory phenomena occur, leading to the growth and neoplasm of tissue elements, as in echinococcosis. The General complex of pathomorphological changes in helminthiasis is currently regarded as a manifestation of allergies and immune suppression. In this connection, there is an almost important question about the mechanisms of formation of manifestations of helminthiasis in the form of specific syndromes that determine the correctness of their diagnosis. These syndromes and their changes in the dynamics of the disease are based on typical pathological processes (dystrophy, local circulatory disorders, myocarditis, inflammation, allergies, immune deficits, etc.).
Keywords: pecilomycosis; lambs; cenurosis; cardiopathy leucoformula